Eksperimental Penambahan Flywheel Sistem Penggerak Mesin Las Gesek Rotari Dengan Variasi Dimensi Permukaan Gesek Pada Pengelasan Gesek Rotari. - Ichsan Rahmadani Syawal; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Rotary friction welding is one of mechanical welding by utilizing the friction of the two joint surfaces to cause heat which is used for the welding connection process. The friction surface afface the rate of heat flow generated from the torque and rotation an axial force (forging) to suppress the friction surfaceThe occurrence of pulses (shock power) at each stage of the friction welding process results in excessive load on the driving motor. In this study theshape and dimensions of the surface, namely the length of the constant champer, 4 mm with angular variations of 150, 300,450 as well as varying the addition of the flywheel to the drive system. Optimal welding results fromspecimen 45,specimens using type II flywheel with tensile strength of 480.44 MPa.Keywords: flywheel, friction surface, rotary friction welding, pulse rate, forging